YouTube as a Source of Health Information on Urinary Incontinence: A Content, Reliability, and Quality Analysis - İlker Çelen; Adil Emrah Sonbahar; Ömür Erdem Akkaya (International Journal of Sexual Science, 2026)
Objective: To evaluate the content, reliability, and quality of YouTube videos on urinary incontinence (UI) and to compare content produced by professional and non-professional sources in terms of quality and popularity. Material and Methods: In this cross-sectional study, the first 100 videos for each of the keywords “urinary incontinence”, “urine leakage”, and “overactive bladder” (300 videos in total) were screened on YouTube. After applying the exclusion criteria, 68 videos were analyzed. This study was limited to English-language videos. Videos were classified according to content and uploader source; uploaders were grouped as professional and non-professional. Quality was assessed by two independent raters using a study-specific modified 18-point scale adapted from DISCERN and the Global Quality Scale (GQS), which has not been formally validated. Viewing rate and the Video Power Index (VPI) were calculated to reflect popularity. Mann-Whitney U, Chi-square/Fisher tests, and the intraclass correlation coefficient (ICC) were used for statistical analysis. Results: Treatment procedures were the most common content (44.1%), and 38.2% of the videos were uploaded by physicians. The median quality score was 11.5 (range 4–18). The professional group had a significantly higher quality score than the non-professional group (median 13.0 vs 7.5; p < 0.001). Although VPI tended to be higher in the non-professional group, the difference was not significant (18.4 vs 11.6; p = 0.112). Inter-rater agreement was high (ICC = 0.88). Conclusion: Physicians were the single most frequent uploader category (38.2%), and professional sources produce higher-quality content; however, professional-source videos did not demonstrate significantly higher popularity metrics compared with non-professional sources. Health professionals should produce evidence-based content and guide patients toward reliable sources.